Synergism of selected flavonoids in inflammation - Harasstani, Omar Abdul Hafiz (2012)
Inflammation is characterized by the release of various pro-inflammatory mediators, including the free radical nitric oxide (NO), prostaglandin E2 (PGE2) and tumor necrosis factor alpha (TNF-a) from stimulated macrophage cells. Sustained release of these mediators can lead to chronic diseases, tissue injury and multiple organ dysfunction syndrome (MODS). Thus, suppression of these mediators is a useful strategy for the treatment of chronic inflammatory diseases. The use of naturally abundant flavonoid compounds is widely reported to have anti-inflammatory, anticancer, anti-oxidant and estrogenic effects. In particular, chrysin, kaempferol, morin, silibinin, quercetin, diosmin and hesperidin are known to alleviate the generation of key pro-inflammatory mediators. Several of the above mentioned flavonoids have shown biological benefits on models of inflammation. Nevertheless, the combinatorial effects of these flavonoids have not been reported. In this study, the synergistic effects of several flavonoid combinations on secretion of major pro-inflammatory mediator from lipopolysaccharide (LPS)-stimulated RAW264.7 cells as a cellular model of inflammation, were investigated. To further assess the therapeutic efficacy of flavonoid combination during the progression of sepsis, survival studies against polymicrobial sepsis in ICR mice were done as an animal model of inflammation. Prior to in vivo experiments, the effects of all compounds on NO, PGE2 and TNF-Ct secretion from LPS-stimulated RAW 264.7 cells were determined by ELISA and Griess assay; as well as cellular viability by MTT assay. After assessing and obtaining the IC50 values, flavonoids that expressed inhibitory effects, in at least two out of the three mediators, were combined in a series of fixed IC50 ratios and reassessed to generate dose response curves. Flavonoid combination that exhibited highest synergistic potency as detected by isobolographic analyses, were employed to further investigate its effects in an animal model of sepsis by cecal ligation and puncture (CLP)-induced septic shock in ICR mice. Key inflammatory 'mediators secreted from septic mice were measured through ELISA and fluorometric determinations; and pharmacological effects upon vital organs were investigated. Chrysin, kaempferol, morin and silibinin were found to have an adequate potency to produce dose-response effects upon at least two out of the three mediators assayed. Significant synergistic effects have been observed among combinations of the flavonoids mentioned above. In particular, the chrysin / kaempferol combination significantly synergized to increase the potency of inhibiting the mediators NO, PGE2 and TNF-Ct secreted from LPS-stimulated RAW 264.7 cells with IC50 = 2.27IlM, 2.281lM and 20.531lM respectively, as well as a 29% significant increase in survival rate in CLP-induced septic shock in ICR mice. Conclusively, this study demonstrated that chrysin / kaempferol combination significantly synergized to increase the anti-inflammatory activity through inhibition of several mediators which contributed to improved survival rate. These fmdings suggest that chrysin / kaempferol combination has reasonable potential as a natural approach in treating inflammation. Further studies are required to investigate the underlying mechanisms involved during inflammation.